Cardiomyopathy associated with the Ala143Thr variant of the α-galactosidase A gene - Valtola Kati; Nino-Quintero Juanita; Hedman Marja; Lottonen-Raikaslehto Line; Laitinen Tomi; Maria Maleeha; Kantola Ilkka; Naukkarinen Anita; Laakso Markku; Kuusisto Johanna (BMJ Publishing Group, 2025)
Objective
To investigate whether the Ala143Thr variant of the α-galactosidase A gene (A143T/GLA), with conflicting interpretations of pathogenicity, is associated with Fabry cardiomyopathy.
Methods
The index patient, a woman in her 60s with cardiomyopathy, was screened for variants in 59 cardiomyopathy-related genes. A143T/GLA, the only rare variant found, was screened in 10 relatives. GLA activity and lyso-Gb3 levels were measured and echocardiography was performed in 8 of 9 subjects carrying A143T/GLA. Cardiac magnetic resonance (CMR) imaging and 18F-fluorodeoxyglucose (FDG) positron emission tomography/CT (PET/CT) were performed in four adult A143T/GLA carriers. Endomyocardial biopsy was obtained from two adult A143T/GLA carrying sons of the index patient.
Results
The index patient and her elder son had a pacemaker implantation because of sick sinus syndrome and atrioventricular block. GLA activities were decreased to 25%–40% of normal in both sons and one granddaughter. Lyso-Gb3 levels were elevated in both sons. In CMR, the index patient and her two sons had left ventricular (LV) hypertrophy and/or dilatation. The elder son had late gadolinium enhancement, high CMR-derived T1 time and positive FDG signal in PET/CT in the basal inferolateral LV wall. The younger son had low T1 time and the mother had positive FDG signal in PET/CT in the basal inferolateral LV wall. Endomyocardial biopsy of both sons showed myocardial accumulation compatible with glycolipids in light and electron microscopy, staining with anti-Gb3 antibody available for the younger son. Five female relatives with A143T/GLA had no cardiomyopathy in cardiac imaging.
Conclusions
A143T/GLA is likely a late-onset Fabry cardiomyopathy causing variant with incomplete penetrance.